Politics of Law Enforcing Death Sentence Based on the Benefit of Law - et al., Fauzun Nihayah (International Journal of Advanced Science and Technology, 2019)
The application of death sentence still creates problems due to the ineffectiveness of deterrent effects in raising fear amidst the society so that people will not do the same crime. The practice of death sentence does not lower the number of extraordinary crimes that threaten the instability of a country and human safety, such as corruption, narcotics, and terrorism. Death sentence is enforced to fight crime against humanity or extraordinary crime. The enforcement of death sentence is also related to the effectiveness of law enforcement. In order to build a model of death sentence system, Islamic law becomes the reference to realize the principle of law utility. The essential purpose of Islamic sharia is benefit. There is no single rule in the Quran or Sunnah that does not bring benefit.